1983
DOI: 10.1111/j.1600-0404.1983.tb04561.x
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol and acetylsalicylic acid in migraine prophylaxis

Abstract: The aim of this double-blind crossover study was to compare the prophylactic effect of acetylsalicylic acid (ASA) with that of propranolol (PRP) in the treatment of migraine. Plasma concentrations of the two drugs were measured in order to investigate a possible relationship to the clinical effect. Compared to the pretreatment period, PRP and ASA reduced migraine index, frequency, duration, severity of attacks and headache days. Due to the limited number of patients, our results should be cautiously interprete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Only Baldrati et al 26 reported that there was an inverse association between severity and aspirin use. Benseñor et al 19 and Baldrati et al 26 reported on the duration of migraine episodes as an outcome. Baldrati et al 26 found an inverse association, while Benseñor et al 19 found a direct association that was not significant.…”
Section: The Effectiveness Of Aspirin For Prophylaxis Of Migrainementioning
confidence: 99%
See 4 more Smart Citations
“…Only Baldrati et al 26 reported that there was an inverse association between severity and aspirin use. Benseñor et al 19 and Baldrati et al 26 reported on the duration of migraine episodes as an outcome. Baldrati et al 26 found an inverse association, while Benseñor et al 19 found a direct association that was not significant.…”
Section: The Effectiveness Of Aspirin For Prophylaxis Of Migrainementioning
confidence: 99%
“…Benseñor et al, 19 Buring et al, 21 Peto et al, 17 O'Neil et al, 31 Baldrati et al 26 and Hosman-Benjaminse et al 27 reported on aspirin as a single active treatment for migraine. All these studies, except for that of Benseñor et al, 19 reported that there was an inverse association between aspirin use and migraine frequency.…”
Section: The Effectiveness Of Aspirin For Prophylaxis Of Migrainementioning
confidence: 99%
See 3 more Smart Citations